Organic persistent room temperature phosphorescence enabled by carbazole impurity - Brannan, Alexander C.; Phuoc, Nguyen Le; Linnolahti, Mikko; Romanov, Alexander S. (Frontiers in Chemistry, 2023)
The molecular design of metal-free organic phosphors is essential for realizing persistent room-temperature phosphorescence (pRTP) despite its spin-forbidden nature. A series of halobenzonitrile–carbazoles has been prepared following a one-pot nucleophilic substitution protocol involving commercially available and laboratory-synthesized carbazoles. We demonstrate how halo- and cyano-substituents affect the molecular geometry in the crystal lattice, resulting in tilt and/or twist of the carbazole with respect to the phenyl moiety. Compounds obtained from the commercially available carbazole result in efficient pRTP of organic phosphors with a high quantum yield of up to 22% and a long excited state lifetime of up to 0.22 s. Compounds obtained from the laboratory-synthesized carbazole exhibit thermally activated delayed fluorescence with an excited state lifetime in the millisecond range. In-depth photophysical studies reveal that luminescence originates from the mixed locally excited state (3LE, nπ*)/charge transfer state.